The Formation and Sequestration of Nonendogenous Ketocarotenoids in Transgenic Nicotiana glauca. Issue 3 (30th January 2017) - Mortimer, Cara L.; Misawa, Norihiko; Perez-Fons, Laura; Robertson, Francesca P.; Harada, Hisashi; Bramley, Peter M.; Fraser, Paul D.
Abstract : In Nicotiana glauca, plastids adapt to sequester nonendogenous carotenoids, demonstrating the robustness of plant metabolism to these changes. Abstract: Ketolated and hydroxylated carotenoids are high-value compounds with industrial, food, and feed applications. Chemical synthesis is currently the production method of choice for these compounds, with no amenable plant sources readily available. In this study, the 4, 4′ β-oxygenase ( crtW ) and 3, 3′ β-hydroxylase (c rtZ ) genes from Brevundimonas sp. SD-212 were expressed under constitutive transcriptional control in Nicotiana glauca, which has an emerging potential as a biofuel and biorefining feedstock. The transgenic lines produced significant levels of nonendogenous carotenoids in all tissues. In leaf and flower, the carotenoids (∼0.5% dry weight) included 0.3% and 0.48%, respectively, of nonendogenous ketolated and hydroxylated carotenoids. These were 4-ketolutein, echinenone (and its 3-hydroxy derivatives), canthaxanthin, phoenicoxanthin, 4-ketozeaxanthin, and astaxanthin. Stable, homozygous genotypes expressing both transgenes inherited the chemotype. Subcellular fractionation of vegetative tissues and microscopic analysis revealed the presence of ketocarotenoids in thylakoid membranes, not predominantly in the photosynthetic complexes but in plastoglobules. Despite ketocarotenoid production and changes in cellular ultrastructure, intermediary metabolite levels were not dramatically affected. The study illustrates the utility of Brevundimonas sp. SD-212 CRTZ and CRTW to produce ketocarotenoids in a plant species that is being evaluated as a biorefining feedstock, the adaptation of the plastid to sequester nonendogenous carotenoids, and the robustness of plant metabolism to these changes.